Alternative Splicing-Related Factor YT521: an Independent Prognostic Factor in Endometrial Cancer. Issue 4 (1st May 2010) - Zhang, Bo; Zur Hausen, Axel; Orlowska-Volk, Marzenna; Jäger, Markus; Bettendorf, Herta; Stamm, Stefan; Hirschfeld, Marc; Yiqin, Ouyang; Tong, Xiaowen; Gitsch, Gerald; Stickeler, Elmar
Abstract : Background: YT521 is a splicing factor involved in alternative splicing regulation of several tumor biological important genes. Two messenger RNA (mRNA) isoforms due to YT521 exon6 alternative splicing exist, with so far unknown functional consequences. Further evidence exists for a direct influence of YT521 expression in tumorigenesis because its mRNA level is changed in tumors compared with physiological tissue. We investigated the potential impact of YT521 expression on tumor biological parameters in endometrial cancer (EC). Methods: Real-time reverse transcription-polymerase chain reaction specifically detecting YT521 exon6-retention and exon6-skipping mRNA isoforms and immunohistochemistry were performed in a cohort of 130 EC tissue samples. Results: Whereas YT521 exon6-retention mRNA was detectable in 86 (66.2%), the exon6-skipping isoform mRNA was expressed in only 8 (6.2%) of all EC samples. On the protein level, 104 (80%) of EC samples showed nuclear expression. The mRNA levels of exon6-skipping isoform were not correlated to any of the clinicopathological parameters of EC. In contrast, YT521 exon6-retention mRNA expression was positively correlated to metastasis ( R = 0.196, P = 0.026) and inversely correlated to the protein expression levels ( R = −0.205, P = 0.019). In univariate analyses, higher levels of YT521 exon6-retention mRNA were correlated to a poorer progression-free survival ( P = 0.003), and this is confirmed by multivariate analyses ( P = 0.019). The negative YT521 protein expression was correlated to poorer overall and disease-specific survival ( P = 0.036 and P = 0.034), respectively, in univariate analyses. They are also confirmed by multivariate analyses ( P = 0.021 and P = 0.010, respectively). Conclusions: We characterized for the first time in a clinical setting a new but rare exon6-skipping mRNA splicing isoform of YT521. Furthermore, we identified YT521 as a potential new independent prognostic factor for patients with EC: the lack of YT521 protein in tumor cells was highly predictive for a poor overall and disease-specific survival and independent from the histological subtypes.